2021
DOI: 10.3390/plants10061237
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Characterization of Hemp Flour (Cannabis sativa L.) from Dacia Secuieni and Zenit Varieties, Compared to Wheat Flour

Abstract: The advanced characterization of flour from hemp seeds (edible fruits of Cannabis sativa L.) from the Dacia Secuieni and Zenit varieties, compared to wheat flour, was studied in this research. The aim was to present the characterization of 2 varieties, out of the 70 accepted in Europe, for human consumption. The varieties selected from hemp meet the THC level requirement (0.3 or 0.2% of the dry weight of the reproductive part of the female flowering plant) in seeds. Hemp flour was obtained by grinding. The flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 39 publications
3
19
0
Order By: Relevance
“…As the amount of hemp flour in the bread increase, a decrease in the moisture content was observed. This decrease is due to the low humidity of the hemp flour used 4.49% for hemp flour variety Dacia Secuieni, respectively 4.98% for hemp flour variety Zenit [ 29 ]. The same decreasing trend was reported by Mikulec et al [ 52 ] for hemp bread, but they started from a higher humidity of the control sample (45.36%).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As the amount of hemp flour in the bread increase, a decrease in the moisture content was observed. This decrease is due to the low humidity of the hemp flour used 4.49% for hemp flour variety Dacia Secuieni, respectively 4.98% for hemp flour variety Zenit [ 29 ]. The same decreasing trend was reported by Mikulec et al [ 52 ] for hemp bread, but they started from a higher humidity of the control sample (45.36%).…”
Section: Resultsmentioning
confidence: 99%
“…It can be seen that it a decrease can be observed with the addition of hemp flour. Most studies performed on hemp seeds or flours obtained from hemp seeds reported the presence of an unsaturated fatty acid content of up to 90% [ 21 , 29 , 61 ]. It is known that the consumption of fatty acids is closely related to the occurrence of coronary heart disease, metabolic syndromes and changes in the intestinal microbiota, while the consumption of unsaturated fatty acids has health-improving effects [ 62 , 63 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations